The Validity Of Learning Motivation On Learning Independence Of Class Xii Students Of Smk N 1 Sintoga - Yunita, Syafrina; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
The purpose of this research was to find out whether there is a relationship between learning motivation and student learning independence in the subject of Indonesian cakes and pastries in class XII SMK N 1 SINTOGA.This type of research is quantitative research with the nature of the research is correlation or relationship. The population in this study were class XII students with a total of 79 students. Members of the sample in this study were 31 students who were selected using the Proportional Random Sampling technique. The data collection technique used in this study was a questionnaire. The data analysis technique in this study uses the Product Moment correlation formula. Based on the results of statistical calculations, it can be seen that students' learning motivation is in the medium category, namely 41.93% and learning independence is in the moderate category, namely with a value of 35.49%. The results of this study are based on the results of research that has been carried out using product moment correlation analysis. It is known that the correlation coefficient between learning motivation (X) and learning independence (Y) is 0.752 which indicates an adequate correlation. The existence of a relationship between learning motivation and learning outcomes is evidenced by obtaining a positive correlation coefficient, which means there is a positive relationship. The correlation that occurs is significant because the obtained tcount is greater than ttable, namely 6.146 > 2.045 at a significance level of 5% with dk 29. The results of data analysis show that there is an influence between learning motivation variables on student learning independence.